A RANDOMIZED, DOUBLE-BLIND TRIAL OF ABATACEPT (CTLA4-IG) FOR THE TREATMENT OF GIANT CELL ARTERITIS - Langford, Carol A. (Arthritis Rheumatol, 2017)
OBJECTIVE: To compare the efficacy of abatacept to placebo for giant cell arteritis (GCA). METHODS: In this multicenter trial, patients with newly-diagnosed or relapsing GCA were treated with abatacept 10 mg/kg IV on days 1, 15, 29, week 8, together with prednisone. At week 12, patients in remission underwent a double-blinded randomization to continue monthly abatacept or switch to placebo. Patients in both study arms received a standardized prednisone taper with discontinuation of prednisone at week 28. Patients remained on their randomized assignment until meeting criteria for early termination or until 12 months after enrollment of the last patient. The primary endpoint was duration of remission (relapse-free survival). RESULTS: Forty-nine eligible patients with GCA were enrolled and treated with prednisone and abatacept; forty-one reached the week 12 randomization and underwent a blinded randomization to abatacept or placebo. Prednisone was tapered using a standardized schedule reaching 20 mg daily at week 12 with discontinuation in all patients at week 28. The relapse-free survival at 12 months was 48% for those receiving abatacept and 31% for those receiving placebo (p=0.049). A longer median duration of remission was seen with abatacept (9.9 months) compared to placebo (3.9 months, p=0.023). There was no difference in the frequency or severity of adverse events between treatment arms, including infection. CONCLUSIONS: In patients with GCA the addition of abatacept to a treatment regimen with prednisone reduced the risk of relapse and was not associated with a higher rate of toxicity compared to prednisone alone.